ALGORITMA LEAST RECENTLY USED UNTUK PEMBENTUKAN CACHE DALAM PENGAKSESAN WEB SERVICE STUDI KASUS TRANSJOGJA - Adi Nugraha, Kristian; Susanto, Budi; Rachmat Chrismanto, Antonius (Proceedings of KNASTIK, 2012)
Transjogja, a busway transportation system, is widely used by people for traveling inYogyakarta. Because of increasing number of Transjogja shelters, using Transjogjabecomes more and more complicated for people. Therefore, the authors propose asolution by designing a location-based mobile application, which can provideinformation about Transjogja. The system is built using a Web Service in order tosupport a large number of outstanding mobile platforms. For the optimization of WebService access, the authors implement a cache in the client application in order tospeedup Web Service access time.